The law of flowing water grouting travel and sedimentary plugging under the influence of many factors - Fuyu Wang; Jiafan Zhang; Xiangrui Qin; Huimei Zhang (Scientific Reports)
Abstract Engineers face significant challenges in determining the grouting parameters and evaluation criteria for environments with flowing water, which has become an urgent matter of concern. Due to the intricate nature of grouting flow and diffusion in practical grouting engineering, numerous fluid-related issues cannot be effectively resolved solely through theoretical analysis or the direct application of fundamental equations. Therefore, it is necessary to employ experimental methods to visually assess and explain these phenomena. In this study, a unique dynamic water grouting test equipment based on 3D printing was designed to evaluate the dynamic grouting travel in cracked rock with flowing water. The influences of fractal dimension, water flow rate, grouting flow rate, and water–cement ratio on the grouting diffusion properties of fractured rock with flowing water were extensively explored. The test demonstrates that the migration and diffusion of grout in the finite boundary fracture can be split into two stages, namely, the circumferent diffusion stage without lateral boundary and the boundary diffusion stage. According to each working circumstance, the diffusion patterns in the process of grouting water plugging are categorized into three types: cross-section, comet, and elongated streamline. A stagnant flow zone was developed in the valley region of the fracture, in which additional particles were deposited. High shear stress was distributed toward the apex area, where few particles were deposited. The experimental results corroborated these observations. The study of the range of grouting diffusion and transport patterns in 3D rough fissures can provide useful insights and guidance for the selection of grouting parameters in grouting engineering practice.